2018
DOI: 10.14742/ajet.2957
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the dimensionality and educational impacts of integrated ICT literacy in the higher education context

Abstract: The purpose of this paper is threefold: first, to introduce a conceptual model for assessing undergraduate students' integrated information and communication technology (ICT) literacy capacity that involves 12 items generated from the modified version of the Australasian Survey of Student Engagement (AUSSE) questionnaire (Coates, 2010); second, to illustrate the construct validity and internal consistency of the model as implemented in a sample of undergraduate students (n = 536) enrolled in two colleges withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
0
27
0
2
Order By: Relevance
“…Katz and Macklin (2007) claim there is no relationship between digital skills and academic performance, and others (e.g. Tadesse et al 2018) have pointed out that digital skills are related to school outcomes, and proposed that approaches to digital skills must survey cognitive factors related to students, since "measuring one without the other may ignore significant interactions between the two, potentially distorting the results" (ibid. p. 98).…”
Section: The Research Problem and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Katz and Macklin (2007) claim there is no relationship between digital skills and academic performance, and others (e.g. Tadesse et al 2018) have pointed out that digital skills are related to school outcomes, and proposed that approaches to digital skills must survey cognitive factors related to students, since "measuring one without the other may ignore significant interactions between the two, potentially distorting the results" (ibid. p. 98).…”
Section: The Research Problem and Hypothesesmentioning
confidence: 99%
“…Previous research has shown inconsistent results regarding whether digital skills are related to academic achievement or not (e.g. Tadesse et al 2018). Tadesse et al (2018) argued that digital skills should not be approached in a vacuum, but be considered in conjunction with students' cognition and interactions, since ignoring these aspects might distort the results (ibid.).…”
Section: Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Switching from the old medium of assessment to the new one -that is conversion from paper-based testing to computer-based data collection -is in progress in a number of ability and skills areas. Regarding the educational setting, besides students' -both in secondary and higher educational settings -, teachers' ICT or digital literacy and competence have been assessed using computerised data collection methods and even recent research with ICT literacy in its focus might still stick to digital versions of self-reported questionnaires (Al Khateeb, 2017;Tadesse, Campbell, & Gillies, 2018).…”
Section: The International Context Of Assessing Ict Literacymentioning
confidence: 99%